2023
DOI: 10.3390/pediatric15040060
|View full text |Cite
|
Sign up to set email alerts
|

Association between Children’s Difficulties, Parent-Child Sleep, Parental Control, and Children’s Screen Time: A Cross-Sectional Study in Japan

Yusuke Arai,
Daimei Sasayama,
Kazuhiro Suzuki
et al.

Abstract: Children’s screen time may affect their growth and development. However, differences in the impact of various psychiatric and psychological factors on children’s screen time is a research gap. This study aimed to explore the differences in the influence of related factors affecting children’s screen time based on their sleep, difficulties, and parental control among Japanese elementary and junior high school students. A cross-sectional survey was conducted among parents in Japan. Data on screen time duration, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Furthermore, employing an automatic time-limiting feature on digital devices may be a practical approach to decrease screen time. This aligns with reports that suggest significantly shorter screen time among users of this feature than among non-users (Arai et al, 2023), underscoring its potential efficacy as a therapeutic tool. The second key contribution is our discovery that enforced screen time restrictions following sleep hygiene education did not result in adverse events such as increased irritability or family conflict.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, employing an automatic time-limiting feature on digital devices may be a practical approach to decrease screen time. This aligns with reports that suggest significantly shorter screen time among users of this feature than among non-users (Arai et al, 2023), underscoring its potential efficacy as a therapeutic tool. The second key contribution is our discovery that enforced screen time restrictions following sleep hygiene education did not result in adverse events such as increased irritability or family conflict.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the history of the patient, we identified nighttime media use as the main causal factor for his chronic insomnia; thus, we emphasized the importance of avoiding nighttime media use. Additionally, we explained the findings of a recent cross-sectional study, which showed that children who use screen time restrictions on their digital devices have shorter screen time compared to those who do not (Arai et al, 2023). This led the patient to introspect on the difficulty of self-managing media use.…”
Section: Therapeutic Interventionmentioning
confidence: 87%